The Utilization of YouTube Channels in Teaching Listening and Speaking Skills to Non-Native Arabic Speakers - Mubarok, Alfian; Tabrani, Ach.; Marina, Silvia; Alfarisi, Usamah Mujahid; Ayyubi, Shalahuddin Al; Hably, Roby (Borneo Journal of Language and Education, 2025)
Listening and speaking are two essential skills in learning Arabic as a foreign language. However, learners in Indonesia often face difficulties in mastering these skills due to limited direct interaction with native speakers and the linguistic differences between Arabic dialects and the Indonesian language. This study aims to explore the use of YouTube as an alternative learning platform to develop Arabic listening and speaking skills. Employing a qualitative-descriptive approach, this research uses documentation and content observation techniques to analyze five selected YouTube channels: Ahdor, Akhdar, Tālek, Al-Jazeera, and Al-‘Arabiyyah Lil-Jāmi’. The data were analyzed qualitatively to identify the linguistic and pedagogical benefits offered by each channel. The findings indicate that the visual and auditory content of YouTube is effective in enhancing students’ listening comprehension, improving pronunciation, enriching vocabulary, and encouraging active imitation of native speakers in real communicative contexts. Moreover, the visual features contribute to a deeper linguistic understanding by linking language to situational contexts.